Use of biomonitors for the identification of heavy metals emission sources - Wannaz, Eduardo Daniel (2012)
Heavy metals accumulation by Tillandsia capillaris was measured to identify their main emission sources in the province of Córdoba, Argentina. Samples of T. capillaris collected over three years at different sites were analysed by flame atomic absorption spectrometry to determine the amounts of Cu, Fe, Ni, Mn, Pb and Zn. The sampling sites were categorized according to land use, anthropic activities and/or distance from the potential heavy metal emission sources. We found that the concentration of heavy metals in the study area is mainly driven by industrial activity while traffic contributed only to the levels of Zn. In addition, we observed a strong relationship between a diffuse emission source and the content of Pb accumulated on the biomonitors which could be attributed to dove hunting activities. Future studies are needed to confirm this hypothesis.